Quantification and discovery of PCR inhibitors found in food matrices commonly associated with foodborne viruses - Cassandra Suther; Matthew D. Moore (Food Science and Human Wellness)
Human norovirus is the leading cause of foodborne illness globally. Detection and quantification of norovirus commonly involves the use of reverse transcriptase quantitative polymerase chain reaction (RT-qPCR); however, the presence of inhibitory compounds in foods limit detection and accurate quantification. Although some studies have been done on PCR inhibitors from foods, many of them are over a decade old and do not investigate inhibition in contemporary one-step RT-qPCR-based detection chemistries. The purpose of this work was to quantify the degree of inhibition that occurs from inhibitory compounds found in produce (pectin) and mollusks (hemocyanin, glycogen)—foods commonly associated with norovirus outbreaks. RT-qPCR reactions containing different amounts of genomic bacteriophage MS2 RNA, a norovirus surrogate, were spiked with different concentrations of pectin (0.0625%–0.25% w/V), glycogen (1.25%–10%), and hemocyanin (0.0625%–0.25%). Past research has implicated glycogen as an inhibitory compound in oysters; however, even high levels of glycogen (10%) had no significant effect (P > 0.05) on amplification. Conversely, both pectin and hemocyanin caused complete inhibition at 0.25%, with no significant inhibition observed at 0.0625% (P < 0.05). Hemocyanin is abundant in the hemolymph of mollusks and previously untested as a PCR inhibitor. This work demonstrates that pectin and hemocyanin should be considered when testing produce and mollusk samples with PCR-based methods. Keywords: PCR inhibition, PCR false negatives, Norovirus detection, Hemocyanin, Pectin